Industrial Relations and Human Resource Management in the Digital Era at PT. Telkom Akses Bali - Dewi, Kadek Christina Oktavia; Santoso, R. Tri Priyono Budi (LPPM Universitas Dhyana Pura, 2025)
Industrial relations in the digitalization era have a significant influence on employee performance, especially human resources, based on digital technology. This situation has a significant impact on employee productivity in companies that implement digital technology models such as PT. Telkom Access in Bali. The interconnectedness of industrial relations tends to have a significant impact on companies in Human Resource Management (HRM), which is a strategic factor in maintaining company performance, productivity, and stability. The purpose of this study is to measure the influence of the correlation between industrial relations and human resource management at PT. Telkom Access Bali. This aims to identify the policies governing the relationship system formed among actors in the service production process, including workers, employers, and the government. The method in this research uses an exploratory qualitative interview approach supported by the experience of companies implementing policies in digital systems. Interviews with 30 employees revealed that industrial relations and human resource management at PT. Telkom Akses Bali found that the process of planning, organizing, directing, and controlling the workforce has been implemented well to achieve company goals effectively and efficiently in the digital era. The conclusion of this study shows that industrial relations with the state of human resources in the digital era are optimal, but have not had a significant impact on the company at PT. Telkom Access Bali. Therefore, it is necessary to seek alternative solutions to optimize and improve performance assessment in industrial relations.